The Labor Market and the COVID-19 Outbreak in Vietnam : Impacts and Lessons Learned for Social Protection - World Bank (World Bank, Washington, DC, 2021)
This note summarizes the impacts of the Coronavirus disease 2019 (COVID-19) outbreak on Vietnam’s labor market in 2020 and evaluates the social protection response to identify lessons learned for future crises. Vietnam’s labor market was shaken by the outbreak in 2020. But an effective containment strategy and a resilient economy mitigated the impact on Vietnam’s labor market, allowing for recovery in the second half of 2020. Vietnam deployed social protection measures to mitigate the impacts on households and firms from disruptions to the labor market that included a package of income support and wage subsidies for households and firms. Fairly strict targeting and eligibility requirements and implementation challenges meant that policy measures were not as effective as hoped. The policy response likely overlooked some impacted groups, and policy makers will likely have struggled to scale up the response in case of a deeper or longer crisis. By revealing these challenges, the COVID-19 policy response has made clear the urgency of reforms to strengthen Vietnam’s social protection system for both normal and crisis times.